Comparison of mechanical energy transfer during right-forward lunge between female amateur and professional badminton players - Soheila Safavi; Rahman Sheikhhoseini; Sajjad Abdollahi (BMC, 2023)
Abstract Background Regarding their skill levels, badminton players present different movement patterns during front and right lunging. The main objective of this study was to compare the mechanical energy transfers attributable to right-forward lunges between amateur and professional badminton players to study variations in mechanical efficiency at various skill levels. Method In this cross-sectional study, twenty female badminton players were recruited (Professional group n = 10 and Amateur group n = 10). The kinematics and kinetics of the lower extremities were recorded while performing right-forward lunges using Vicon motion capture and Kistler force plates. Mechanical energy expenditures (MEE) were extracted in eccentric transfer, concentric transfer, and no-transfer phases for the hip, knee, and ankle joints. At each joint, mechanical energy compensations (MEC) were also determined. Independent samples t-tests were used to analyze data at a significance level of α = 0.05. Result Regards to mechanical energy expenditures at the initial heel contact phase, the professional players demonstrated statistically significant more ankle no-transfer (p < 0.003), less knee concentric transfer (p < 0.026), more knee eccentric transfer (p < 0.001), and less hip no-transfer (p < 0.001). At the same time, the amateur athletes showed significantly more ankle eccentric transfer (p < 0.042) at maximal knee flexion angle time point. Analyzing mechanical energy compensation coefficients showed that the professional athletes had significantly less ankle concentric transfer (p < 0.001), more knee concentric transfer (p < 0.001), more knee eccentric transfer (p < 0.001), and more hip eccentric transfer (p < 0.001) at initial contact phase. While they found to have significantly more ankle eccentric transfer (p < 0.007), less knee concentric transfer (p < 0.001), less knee eccentric transfer (p < 0.001), more hip concentric transfer (p < 0.001), and more hip eccentric transfer (p < 0.001) at maximal knee flexion angle. Conclusion it is shown that the mechanical energy efficiency of the right-forward lunge is skill-related. It seems that altered lunge landing biomechanics may increase the risk of ankle and knee injuries and muscular damages in amateur athletes. It is recommended for amateur players to follow a injury prevention training program that promotes proper lunging technique.